A “Dakwah Kultural dan Moderasi Beragama dalam Masyarakat Multiagama: Studi Pemikiran KH Mustofa Bisri di Desa Tejowangi, Kecamatan Purwosari, Kabupaten Pasuruan” - Moh. Amin Farijallah; Anang Sholikhudin (Bayan lin-Naas : Jurnal Dakwah Islam, 2026)
This study aims to examine the role of cultural da’wah in strengthening religious moderation within the Muslim–Christian community in Tejowangi Village, Purwosari District, Pasuruan Regency. The research employs a descriptive qualitative approach using interviews, observations, and documentation as data collection techniques. The informants consist of Islamic religious leaders, Christian religious leaders, village officials, and local community members selected through purposive sampling. Data analysis was conducted using the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the socio-religious life of the Tejowangi community is harmonious and inclusive. The practice of cultural da’wah is reflected in cross-religious participation in various social and religious activities, including religious celebrations and local cultural traditions. Religious moderation is demonstrated through attitudes of tolerance, social solidarity, and acceptance of local cultural values within the community. In addition, religious leaders play an important role in maintaining social stability by promoting moderate and inclusive religious teachings. This study reveals that cultural da’wah significantly contributes to fostering social harmony within a multi-religious society.